TYPES AND MAIN CHARACTERISTICS OF MONITORING TRAINING OF MODERN ECONOMIC STAFF (Pedagogy of Higher and Secondary Education, 2008)
This article describes types and main characteristics of monitoring of contemporary economical staff.